Platelets Adhere to Sulfatides by von Willebrand Factor Dependent and Independent Mechanisms - Data, Richard E; Williams, Sybil B; Roberts, David D; Gralnick, Harvey R (Thrombosis and Haemostasis, 1991)
Unstimulated human platelets from normal volunteers adhere to sulfatides (galactosylceramide-I3-sulfate) as single cells but do not adhere appreciably to other lipids including gangliosides, neutral glycolipids, phospholipids or cholesterol-3-SO4. Platelet adhesion to sulfatide is saturable and dose-dependent, reaches maximal levels in 90 to 120 min, and is not divalent cation-dependent. Because sulfatides bind von Willebrand factor (vWf) with specificity and high affinity and platelet adhesion to structurally related sulfated glycolipids is approximately proportionate to their ability to bind vWf, we examined whether vWf mediates platelet adhesion to sulfatides. Platelets from a patient with severe Type I von Willebrand’s disease adhere poorly to sulfatides. However, adhesion to levels seen with normal platelets is restored by the addition of vWf. Adhesion of normal platelets can be partially inhibited by a monospecific antibody to vWf. Normal platelet adhesion to sulfatides, however, is not increased following preincubation with vWf. Both vWf binding and platelet adhesion to sulfatides can be inhibited by the sulfated polysaccharide dextran sulfate at low concentration, fucoidan at high concentrations, but not by heparin, fibrinogen, fibronectin, or the synthetic peptides Gly-Arg-Gly-Asp-Ser-Pro or Gly-Arg-Gly-Glu-Ser-Pro. Thus, adhesion to sulfatides appears to be of two types; vWf dependent (50-75%) and vWf independent (25-50%).